The association between oxidative balance score with constipation and diarrhea in US adults: a cross-sectional analysis of NHANES 2007–2010 - Yaoling Cao; Zhihao Yang; Qinqing Tang (BMC Gastroenterology)
Abstract Background Oxidative stress is associated with functional bowel disorders. The Oxidative Balance Score (OBS) is used to represent the overall level of oxidative stress experienced by an individual. Sex differences are exhibited in the occurrence of constipation and diarrhea. This population-based study aimed to examine the association between the OBS, constipation, and diarrhea, among adults in the United States (US), stratified by sex. Methods Using data from the National Health and Nutrition Examination Survey (NHANES) database spanning from 2007 to 2010, a cross-sectional study including 4,462 participants (2,386 males and 2,076 females) was performed to assess the relationship between the OBS, constipation, and diarrhea, among adult men and women in the US. Constipation and diarrhea were identified according to bowel frequency and stool type, as outlined in the Bowel Health Questionnaire. The independent variable was the OBS based on 20 types of dietary and lifestyle components. We conducted a binary logistic regression subgroup analysis by sex, and a univariate subgroup analysis; and used a restricted cubic spline (RCS) to illustrate the relationship between the OBS and abnormal bowel health. Results After adjusting for all covariates, a multivariate binary logistic regression analysis revealed that the OBS was negatively correlated with constipation in males [odds ratios (OR) (95% confidence intervals (CI)): 0.937 (0.888, 0.988), P = 0.017], and diarrhea in females [OR (95%CI): 0.951 (0.916, 0.987), P = 0.009]. RCS analysis identified a negative linear trend between OBS and constipation in males (P for non-linearity = 0.63), as well as between OBS and diarrhea in females (P for non-linearity > 0.05). Conclusion The current study found a negative correlation between the OBS and the risk of constipation in males, along with diarrhea in females. Oxidative stress, gut microbiota, and sex differences may be associated with intestinal dysfunction. These findings suggest that antioxidant-rich dietary modifications may be an effective strategy for preventing constipation in males and diarrhea in females.